The History of Pocomia in Limon (Costa Rica) and Bocas del Toro (Panama). From Late Nineteenth Century to the Present - Alvarado Luna, Axel (2016)
The history of Limon city is completely different from that of Costa Rica. Its cultural, economic, ethnic and even urban origin (background) makes such a big difference that it could be said that it is a country within a country.  One of the causes that clearly illustrate that difference was the construction of the Railroad a major project that connected the capital with the Caribbean side of the country. The people who worked on the railroad were Italians, Chinese, Central Americans, Coolies from India, Blacks from the Caribbean (mainly Jamaicans), and a few adventurers from the Central Valley. Thus Limon became the foundation of culture and traditions, different from the rest of the country. A study will be made of Pocomia, one of the creeds, which was widely diffused in the Caribbean and in other parts of the American Continent where Jamaican immigrants had arrived.